2022
DOI: 10.1097/mnm.0000000000001652
|View full text |Cite
|
Sign up to set email alerts
|

Comparing digital to analog prostate-specific membrane antigen-targeted piflufolastat 18F PET/CT in prostate cancer patients in early biochemical failure

Abstract: Purpose Prostate-specific membrane antigen (PSMA) positron emission tomography/computer tomography (PET/CT) in prostate cancer patients with biochemical failure(BCF) showslimited sensitivity when the prostate-specific antigen(PSA) <0.5 ng/mL. The development of digital PET/CT has greatly improved smaller lesion detection. This study's goal was to compare the performance and clinical value of PSMAtargeted piflufolastat PET/CT for prostate cancer BCF with digital versus analog PET/CT. MethodsIn this retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Despite this evidence, a previous study did not show a significant difference in lesion size between dPET and aPET, although reporting a higher tumor-to-background ratio (TBR) for dPET, therefore resulting in an improved lesion detectability nonetheless [35]. This aspect should also be further investigated using other PSMA tracers, such as 18 F-DCFPyL [38].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Despite this evidence, a previous study did not show a significant difference in lesion size between dPET and aPET, although reporting a higher tumor-to-background ratio (TBR) for dPET, therefore resulting in an improved lesion detectability nonetheless [35]. This aspect should also be further investigated using other PSMA tracers, such as 18 F-DCFPyL [38].…”
Section: Discussionmentioning
confidence: 88%
“…dPET also identified a significantly higher number of pathologic findings (PSMA-RADS ≥ 3) per patient and more multi-metastatic cases (>3 lesions) compared to aPET. Previous literature studies have compared the performance of digital and analog PET/CT in prostate cancer patients [35][36][37][38][39]. Specifically, Alberts et al, in a retrospective evaluation of two matched cohorts of BCR Pca patients undergoing 68 Ga-PSMA-11 imaging (aPET: 88, dPET: 88), found that dPET identified a greater number of pathological findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation